Signaling microdomains in T cells. - Choudhuri, K; Dustin, M (2010)
Sub-micron scale signaling domains induced in the plasma membrane of cells are thought to play important roles in signal transduction. In T cells, agonist MHC-peptide complexes induce small diffraction-limited domains enriched in T cell receptor (TCR) and signaling molecules. These microclusters serve as transient platforms for signal initiation and are required for sustained signaling in T cells, although each microcluster functions for only a couple of minutes. How they are formed, and what mechanisms promote and regulate signaling within TCR microclusters is largely unknown, although it is clear that TCR engagement and dynamic reorganization of cortical actin are involved. Here, we review current understanding of signaling within microclusters in T cells, and speculate on how these structures may form, initiate biochemical signals, and serve as sites of both signal integration and amplification, while also facilitating appropriate termination of TCR and related signaling.